PERAN GEMBALA SIDANG TERHADAP KEPEMIMPINAN DAN PERTUMBUHAN GEREJA DALAM PERSPEKTIF KONSELING PASTORAL - Limeani Zalukhu; Leniani Zalukhu (POIMEN Jurnal Pastoral Konseling, 2022)
The pastor has a very important influence on his church. The leadership of a pastor in a church will affect the growth that occurs in the church. A healthy church is a growing church. However, pastors sometimes neglect to provide guidance so that the church does not grow. If there is no action, an appropriate method of counseling is applied in the church, it will cause a more complicated problem. The purpose of this study is to reveal the role of the pastor on leadership and growth in the church. The problems in this study are as follows: What is the role of the pastor on church leadership and growth in the perspective of pastoral counseling?. The method used in this research is descriptive qualitative. The results used in this study indicate a form of pastoral counseling method given by the pastor to congregation members as leaders and to increase church growth. The existence of pastoral counseling can help the pastor's role in leadership in the church and display a superior character, trustworthy attitude and role model in growing the church.